Iconic Celebration of Charms and Friendship in Poetry: Fálétí’s “Adébímpé Ọ̀jẹ́dòkun” - Michael Oladejo Afoláyan (Yoruba Studies Review)
“Adébímpé Ọ̀jẹ́dòkun” is a heroic poetry with the resemblance of a tragic history. It is a hunter’s dirge, where the griot happens to be a friend to a friend of the fallen hunter. In essence, it is a chant that laments a deep loss of an idol and celebrates the sacred cult of friendship. Here, a friend whose name is unknown, narrates the demise of his friend, Adébímpé Ọ̀jẹ́dòkun. The latter gave his life in pursuit of the killer of his own friend, Inaolaji. The story is that of the mythical character, Adébímpé Ọ̀jẹ́dòkun, eulogized as a great hunter with cult following. His death takes on the appearance of a slap in the face of medicinal charm, charisma, and talismanic efficacy, almost tantamount to “the death of the mythical Yorùbá medicine man’s child in broad day light.” The tragic event calls for lamentations across the land. Even the most callous, capable of “eating the head of the tortoise, and drinking cold-heartedly with the empty shell of the diminutive snail” would hear the tragic narrative and snivel. It’s that bad! Here is the unfolding of the event: Adébímpé Ọ̀jẹ́dòkun, the man of the people would do anything to alleviate the pain and suffering of his people. Any animal attack, a stampede in the farm, an elephant on the rampage or the buffalo with untoward assaults on the people in the distant wood would invoke the wrath of Adébímpé, and his instant intervention was natural. And so came the day when the wild beast would not let peace reign in the neighboring forest, and the person to call to the rescue was no other person than Adébímpé Ọ̀jẹ́dòkun, 86 Michael Oladejo Afoláyan fondly known as “the deadly spirit that roams the wild, son of the Queen Mother.” With deep inquiry, he found it was actually the farmland of his friend that was attacked. He swore by the sacred incantation that there would be no peace for an animal that made waste the farm of his friend, just as “the male pigeon is never at ease to live inside the house; Èmì – the migrant rat, never sleeps in the same nest two nights in a row; and as the case is for the pataguenon monkey to jump from tree to tree restlessly without finding a place to rest . . .” so would it be for the animal that violated the farm of his friend. Friends and neighbors consoled Adébímpé who was hell bent on going after the wild beast that had the audacity to destroy his friend’s farm. Adébímpé must vindicate his friend’s loss. His zeal for the vindication of this friend’s loss brought tears to the eyes of Adébímpé ’s neighbors who had the prior knowledge of the worse that had actually occurred: it was not the farm of Adébímpé ’s friend that was destroyed; it was actually Adébímpé ’s friend, Inaolaji himself, that was killed by the wild beast! As could be expected, Adébímpé was devastated on hearing the bad news. Then and there, he swore not to weep or mourn the loss of his friend, neither would the hunter’s funeral rites be performed for Inaolaji until two things happened: the body of his friend was retrieved and the culprit, the wild beast, was brought to justice by being totally and vindictively annihilated. Anything less, would fail miserably for the hero to mourn the parting of his friend with honor. And so Adébímpé embarked on the journey of honorable vindication. He bade two other hunters to tag along and they headed straight to the deep woods; after all, a hunter-prince never went on a hunting expedition solo. Soon, they found the remains of Inaolaji and secured the body, but Adébímpé swore he would not retreat until the animal that had the audacity to take his friend’s life had its own life taken as well. The journey continued. The search was strenuous. The distance was far afield. Jungles were crossed. Hilly terrains were toiled. Then, the hero apprehended the perpetrator. The battle ensued; and it was fierce. This would be a one-on-one encounter between Adébímpé and the erring beast, a leopard. Adébímpé gave his partners a break, ordered them to stand aloof and watch him and the leopard in an epic fight for life. He anchored the weapon by the trunk of a tree, tucked the sword in the sheath. He was confident he would wrestle the beast with his bare fist to a total submission and round it up with an eventual kill. He resorted to the spell of incantation, binding all spirits of the adder, the pythons, and the minor serpents. The chanting triggered Iconic Celebration of Charms and Friendship in Poetry 87 the wrath of the wild beast, which charged at the hero hunter. It was an all-out war, a mortal skirmish with no end in sight! It was a battle of two hunters – a human hunter facing the animal hunter, each pommeling the other with the killer instinct. Exasperated, Adébímpé resorted back to the power of the word as he emitted precarious incantations that forced the fingernails of the leopard to sink back into their sockets; the tongue glue jammed into the roof of the mouth; the teeth withdrawing and hiding inside the gums of the clenched jaws. It was at this point that the great hunter, Adébímpé, choke-holding the leopard, called on the younger hunters and ordered them to come near and shoot the beast at close range. The nervous hunter was the first to attempt the shoot, emptying the loaded barrel into the leopard, himself falling headlong at the sound of his own gun. Adébímpé hissed and mocked the nervous hunter, informing him of a big miss on so-close a target! He then beckoned on an alternative hunter, swearing he would not let go of the grip of the leopard. The second hunter finished off the animal with the shot right on target with a sniper’s propensity. The leopard lost the battle; fell down and died. Adébímpé then summoned all the hunters to come near and see a bewilderment. It was there he disclosed to them that the earlier nervous hunter did a fatal damage to him because when the hunter shot the leopard nervously, he missed the target but hit Adébímpé. He let them see the flow of blood coming from his torso. They all shouted and cried in despair. The echo of their cries swept through the length and breadth of the jungle. Adébímpé consoled them, tying the fatal shot to fate, against which no one could possibly prevail. He bade his comrades farewell, then slumped and gave up the ghost. Three bodies were brought back from the wood – that of Inaolaji, the one of the leopard, and finally, that of Adébímpé Ọ-̀ jẹ́dòkun, the altruistic hero.